Cognitive Reserve as a Protective Factor of Mental Health in Middle-Aged Adults Affected by Chronic Pain - Delgado-Gallén, Selma; Soler, M. Dolors; Albu, Sergiu; Pachón-García, Catherine; Alviárez-Schulze, Vanessa; Solana-Sánchez, Javier; Bartrés-Faz, David; Tormos, Josep M.; Pascual-Leone, Alvaro; Cattaneo, Gabriele (Frontiers in Psychology, 2021)
Chronic pain is associated with worse mental health and cognitive impairment, which can be a cause or a consequence of brain structure and function alterations (e.g., maladaptive plasticity, antinociceptive system dysregulation). Cognitive reserve reflects the effectiveness of the brain's internal connections and it has been shown to be a protective factor in brain damage, slowing cognitive aging or reducing the risk of mental health disorders. The current study explored the impact of CP on psychosocial factors, MH, and cognition. Furthermore, we aimed to examine the role of CR in the relationship between MH and CP clinical characteristics in middle-aged adults. Four hundred seventy-seven volunteers from the Barcelona Brain Health Initiative completed online surveys on pain, mental health, cognitive reserve, and psychosocial factors (sleep and quality of life). We described the differences in sociodemographic data, psychosocial factors, mental health, and self-perceived cognitive impairment, and neuropsychological assessment, between participants reporting pain compared to those without pain, as well as the main characteristics of the chronic pain group. Finally, to study the role of cognitive reserve in the modulation of the relationship between CP and mental health we compared variables between subgroups of participants with high/low pain intensity and cognitive reserve. Chronic pain was reported by 45.5% of middle-aged adults. Our results showed that participants with chronic pain were older and had worse health status than people without pain. The presence of chronic pain affected working memory, mental health, and daily life activities. Moreover, cognitive reserve moderated the influence of pain intensity on mental health, resulting in less mental health affection in people suffering from high pain intensity with high cognitive reserve. In conclusion, the construct of the cognitive reserve could explain differential susceptibility between chronic pain and its mental health association and be a powerful tool in chronic pain assessment and treatment, principally due to its modifiable nature.